A new mode of SAM domain mediated oligomerization observed in the CASKIN2 neuronal scaffolding protein. Issue 1 (December 2016) - Smirnova, Ekaterina; Kwan, Jamie; Siu, Ryan; Gao, Xin; Zoidl, Georg; Demeler, Borries; Saridakis, Vivian; Donaldson, Logan
Abstract Background CASKIN2 is a homolog of CASKIN1, a scaffolding protein that participates in a signaling network with CASK (calcium/calmodulin-dependent serine kinase). Despite a high level of homology between CASKIN2 and CASKIN1, CASKIN2 cannot bind CASK due to the absence of a CASK Interaction Domain and consequently, may have evolved undiscovered structural and functional distinctions. Results We demonstrate that the crystal structure of the Sterile Alpha Motif (SAM) domain tandem (SAM1-SAM2) oligomer from CASKIN2 is different than CASKIN1, with the minimal repeating unit being a dimer, rather than a monomer. Analytical ultracentrifugation sedimentation velocity methods revealed differences in monomer/dimer equilibria across a range of concentrations and ionic strengths for the wild type CASKIN2 SAM tandem and a structure-directed double mutant that could not oligomerize. Further distinguishing CASKIN2 from CASKIN1, EGFP-tagged SAM tandem proteins expressed in Neuro2a cells produced punctae that were distinct both in shape and size. Conclusions This study illustrates a new way in which neuronal SAM domains can assemble into large macromolecular assemblies that might concentrate and amplify synaptic responses.